Holographic Schwinger Effect with a Rotating Probe D3-Brane - Hao Xu; M. Ilyas; Yong-Chang Huang (Advances in High Energy Physics)
This paper, among other things, talks about possible research on the holographic Schwinger effect with a rotating probe D3-brane. We discover that for the zero temperature case in the Schwinger effect, the faster the angular velocity and the farther the distance of the test particle pair at D3-brane, the potential barrier of total potential energy also grows higher and wider. This paper shows that at a finite temperature, when S5 without rotation is close to the horizon, the Schwinger effect fails because the particles remain in an annihilate state, which is an absolute vacuum state. However, the angular velocity in S5 will avoid the existence of an absolute vacuum near the horizon. For both zero and finite temperature states, the achieved results completely agree with the results of the Dirac-Born-Infeld (DBI) action. So the theories in this paper are consistent. All of these show that these theories will play important roles in future pair production research.